PNAE e agricultura familiar em santa maria/rs: muitos os chamados, poucos os escolhidos - Vieira, Maria Helena Matchin (2014)
The general objective of this work is to identify barriers that limit access of the family farmers to the National School Nutrition Programme (PNAE) in the Municipality of Santa Maria, RS, Brazil. A study case was chosen as a research method because it allows the study of a phenomenon within its real life context and complexities, when the boundaries between phenomenon and context are not clear enough, and in which multiple sources of evidence are used. The instruments to collect data were semi-structured interviews and documentary analysis. A theoretical sample was designed to fulfill the objective. It was composed of 50 Family Farmers, and 5 key informants of the management Programme. The results of the work indicated that the principal obstacle to participate in the Programme by Family Farmers is the traditional historical exclusion of the system that they have suffered. Culturally, this means a rational reluctance to be a part of the public policies. Public Policies need to enhance the small farmers‟ ability to seize opportunities in those policies. Secondly, farmers say that they lack of knowledge about PNAE. Public Policies need to ensure that small farmers have access to information, and that they have a voice through the different organizations and representation on decision making bodies. Thirdly, Family Farmers consider that fairs are the proper way to commercialize their products. They feel more freedom and less pressure of the market and also more self-esteem because they actively participate in the process of selling (empowerment). Public Policies need to study carefully this approach of agricultural commercialization. In doing so, the new economic sociology can provide insights of value, and a partnership with academic institutions would be very useful.